Acid-Triggered Nanoexpansion Polymeric Micelles for Enhanced Photodynamic Therapy - Zhong, Sheng; Chen, Chao; Yang, Guoliang; Zhu, Yucheng; Cao, Hongliang; Xu, Beijian; Luo, Yaoqin; Gao, Yun; Zhang, Weian (ACS applied materials & interfaces, 2019)
Photodynamic therapy (PDT) as a noninvasive and selective treatment technology has presented great potential in cancer prevention and precision medicine, but its therapeutic efficacy is still greatly inhibited by the limitations of photosensitizers (PSs) in the microenvironment such as the aggregation caused quenching (ACQ) of PSs. Herein, we proposed an “acid-triggered nanoexpansion” method to further reduce the aggregation of photosensitizers by constructing acetal-based polymeric micelles. A pH-responsive amphiphilic block copolymer, POEGMA-b-[PTTMA-co-PTPPC6MA] was synthesized by reversible addition–fragmentation chain transfer (RAFT) polymerization and self-assembled into spherical micelles. In the normal physiological environment, the micelles were stable and had good biocompatibility. Upon entry into the acidic microenvironment of the tumor, the acid-responsive hydrophobic 2, 4, 6-trimethoxybenzaldehyde in the micelles hydrolyzed and generated a hydrophilic diol moiety. Although the hydrophility of the micellar core was increased, the assembled structure of block copolymers was not dissociated but expanded. The responsive expansion of the micelles could allow the photosensitizers to well-disperse in the core, whereas more tumor-dissolved oxygen entered the micelles. This phenomenon could provide a better nanoenvironment for photosensitizers to reduce the ACQ of the photosensitizers, leading to more singlet oxygen (1O2) produced under the laser irradiation (650 nm). Both in vitro and in vivo studies have demonstrated that the remarkable photodynamic therapeutic efficacy of acid-responsive micelles could be realized. Thus, the acid-triggered nanoexpansion method might provide more possibilities to develop efficient platforms for treating cancers.